Klasifikasi Kebutuhan Pada Diagram SysML - Oktaviyani, Enny Dwi (Universitas Palangka Raya, 2014)
Requirements engineering activities are more widespread and difficult lead to the increasingcomplexity of software systems. User needs often change sometimes make changes that affect otherneeds and at a later stage. One user requirement modeling that can be used is the SysMLdiagrams. SysML diagrams can be used for the activity of complex software systems. In SysMLdiagrams are requirements diagrams to classify requirements into functional requirements, nonfunctionalrequirements and external interfaces requirements. SysML diagrams help to determinethe order of the most important requirements to be done at the time of implementation. SysMLdiagrams help breaking into the complex requirements of simple requirements and establish ahierarchy that links one needs with other requirements.